Empowering Eco-Innovation Through Digitalization in Startup Enterprises - Jessica Wilson; Erika Erika (Pandawan Sejahtera Indonesia, 2025)
The digital era has created a new landscape for the world of entrepreneurship, where environmental challenges and changes in consumer behavior require business actors, especially startups, to Innovate to create products that are not only competitive but also sustainable. The background of this research is the urgent need for business solutions that support sustainability principles and align with the Sustainable Development Goals (SDGs). This study aims to identify strategic opportunities in the development of eco-innovative products by startups in the digital era, as well as the factors that encourage and hinder their implementation. Using a descriptive qualitative approach, data was collected through literature studies and in-depth interviews with several startup founders operating in the environmental and technology sectors. The results show that the integration of digital technologies, such as the Internet of Things (IoT), e-commerce, and big data, opens up significant opportunities for the development of more efficient, personalized, and affordable eco-friendly products. However, challenges such as limited access to green financing and a lack of sustainability literacy remain major obstacles. The conclusion of this study confirms that the digital era offers significant opportunities for startups to become agents of change through eco-innovative products, provided they are able to integrate environmental values into their business models and utilize digital technology optimally.